A geographic perspective of cuban landscapes - Gebelein, Jennifer (Landscape Series,, 2012)
Beginning in the era of the Spanish conquest and taking the reader right up to the present day, this book focuses on how the landscape of Cuba has changed and evolved into the environment we see today. It illustrates the range of factors - economic, political and cultural - that have determined Cuba's physical geography, and explores the shifting conservation measures which have been instituted in response to new methods in agriculture and land management. The text uses historical documents, fieldwork, Geographic Information System (GIS) data and remotely-sensed satellite imagery to detail Cuba's extensive land-use history as well as its potential future. The author goes further to analyze the manner, speed and methods of landscape change, and examines the historical context and governing agendas that have had an impact on the relationship between Cuba's inhabitants and their island. Gebelein also assesses the key role played by agricultural production in the framework of international trade required to sustain Cuba's people and its economy. The book concludes with a review of current efforts by Cuban and other research scientists, as well as private investors, conservation managers and university professors who are involved in shaping Cuba's evolving landscape and managing it during the country's possible transition to a more politically diverse, enfranchised and open polity.